PERAN SOUTH EAST ASIAN FISHERIES DEVELOPMENT CENTRE (SEAFDEC) DALAM MENANGANI ILLEGAL, UNREPORTED AND UNREGULATED FISHING DI INDONESIA - Mega Puteri Dayu (2020)
IUU Fishing signifies that an activity of exploitation of natural resources can harm the country. And in this research, the authors describe how SEAFDEC is conducting its role as an international organization in the handling of IUU Fishing. To answer the research questions that exist in this research, the authors use the role concept of international organization and IUU Fishing. This research is a qualitative study. The data collection techniques used in this study through the study of the literature. The research method used in this research is to use secondary data. The analytical techniques used in this study are qualitative analytical techniques. And in this research illustrates that there is a role run by SEAFDEC as an international organization as an instrument, arena and actors in addressing the issues IUU Fishing. The role was described through SEAFDEC's to as an instrument for Indonesia in carrying out its foreign political objectives, meetings through discussion forums in the effort to disguise the views to eradicate IUU Fishing and the efforts of SEAFDEC in handling the IUU Fishing.